The Risk of Urinary Tract Infection in Post-Operative Pelvic Organ Prolapse is Increasing in Patients with Shorter Urethral-Anal Distance - Fakhrudit, Emir; Fauzit, Amir; Effendy, Kms Yusuf; Theodorus, Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objectives : The purpose of our study was to find the correlation between urethral-anal distance and urinary tract infection (UTI) after surgery for grade III and IV uterine prolapse. Methods : Cross sectional study of 57 consecutive women who underwent surgery for grade III and IV uterine prolapse Fisher exact test was used to determine independent risk factors. Results : Eight (14%) women developed a UTI. The risk of UTI was significantly increased in women whose distance between the urethra and the anus was less than 50.27 mm, with PR: (95%Cl): 43.75 (6.05-303.61) and p: 0.001. Conclusion: There is correlation between urethral-anal distance and urinary tract infention (UTI) after surgery for grade III and IV uterine prolapse. [Indones J Obstet Gynecol 2013; 1-3: 152-5] Keywords: cystocele, pelvic organ prolapse, rectocele, urinary tract infection, uterine prolapse